Prevalence of Attention Deficit Hyperactivity Disorder Symptoms in Children Who Were Treated at Emergency Service due to Unintentional Injury - Mehmet İz; Veysi Çeri (Emergency Medicine International)
Aim. Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder characterized by severe inattention, hyperactivity, and impulsivity. This research aims to determine the frequency of ADHD symptoms in children who were treated in emergency paediatric services due to unintentional injuries. Method. This study was carried out with children who were treated due to unintentional injuries in an Emergency Department. ADHD symptoms were evaluated using the DSM-IV-based Screening and Assessment Scale for Behavioural Disorders in Children and Adolescents. Results. The study sample consisted of 89 girls (40.1%) and 133 boys (59.9%)—a total of 222 children. The participants ranged from 5 to 18 years of age, and the mean age was found to be 11.5±3 years. According to medical evaluations, the most common diagnosis for the unintentional injuries was soft tissue trauma (41.9%). The mean ADHD and ODD (Oppositional Defiant Disorder) scores of our study sample were, respectively, 19.9±12 and 7.7±5.7. The prevalence of children with possible ADHD was as high as 81.6% (179) and, for ODD, was 62.6% (139), according to cut-off values. Conclusion. Our results pointed out very high levels of ADHD and ODD symptoms among children who were treated at emergency services for accidental injuries. Appropriately screening for ADHD in children with accidental injuries and referring them to child psychiatry units may prevent later accidents and injuries.